Social Networks Usage Among Youth In The Kyrgyz Republic - Z. Zhorobekova; G. Muhametjanova; R. Ismailova (MANAS: Journal of Engineering)
According to statistics, in 2012 there were 767514 social network users in the Kyrgyz Republic, which is the second largest network in Central Asia, after Kazakhstan. The majority of users are females â 60%, mostly of young ages â 19-24. In the scope of this research, it was aimed to study the influence of social networks on the thinking abilities of students, if they consider SN as helpful in education, the level of trust to information on SN and money spend on SN by students. Also, since SN is getting more and more popular among students, the SN addiction level was investigated. Data was collected using online survey forms among youth. The total sample size included into analysis comprised 71 users. We believe that the obtained results will help us to shed a light to the problem of SN usage by students in educational context.